KECEMASAN TOKOH ICIH PRIHATINI DALAM NASKAH DRAMA MONOLOG WANCI KARYA IMAS SOBARIAH: ANALISIS PSIKOLOGI SASTRA - Ratih Dwi Cahyani; Elmustian Elmustian; Dudung Burhanuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : This study discusses the anxiety of Icih Prihatini figures in the script of monologue Wanci works Imas Sobariah based on the approach to psychology literature analyzed. In this study examines the problem formulation what the anxiety experienced by Icih Prihatini figures in the script monologue drama Wanci works from Imas Sobariah. The data source is the goal of this study is the monologue drama script Wanci Imas Sobariah work. The research data I look in form of sentences and dialogue excerpts relating to anxiety figure consists of realistic anxiety, neurotic anxiety and moral anxiety. The research method used is a qualitative method which describes the description data. Technique of collecting data in this research is documentation techniques. Data analysis technique is used, the data reduction, data representation and conclusions must be terminated. The data of this study amounted to 38 data that consists of 12 data realistic anxiety, neurotic anxiety data 12 and 14, the data of the moral by the signs experienced fear in the script monologue Prihatini Icih Wanci Sobariah Imas work.Keywords : Anxiety Figures Icih Prihatini, Script of Monologue Drama Wanci works Imas Sobariah.